PELAKSANAAN PUTUSAN PENGADILAN DALAM PERKARA PENGOSONGAN RUMAH - Syaihul Hakim (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
code of practice for a court decision in a case based on the chapter house emptying in article 1033 (Rv) and article 200 paragraph (11) HIR and article 218 paragraph (2) RBG, which in these articles provides provisions regarding how the house emptying execution that contains certain conditions including: (1) Decision that would have been executed have the force of permanent, (2) The loser still refused to run the contents of the court verdict again him eventhough voluntarily given warning (aanmaning) and the court granted a grace period has been exceeded, (3) Chief of the court where the case is decided upon has issued an order setting the execution.Step to be taken when getting resistance from a third party, basically there are 2 (two), namely: (1) Perform temporary moratorium on execution emptying wan to run, this is done if he believes the resistance/protest is submitted by third parties in the field are based legitimate property rights, or there are indication that lead the physical clashes that could ultimately lead to casualties, (2) Fixed blanking out the execution despite opposition from third parties, if the resistance is not based on legitimate property rights and is only intended to frustrate the execution of emptying, and when the execution started emptying remains no indication that lead to physical clashes can cause casualties.